Carbon and Redox Tolerant Infiltrated Oxide Fuel-Electrodes for Solid Oxide Cells. (26th April 2016) - Skafte, Theis Løye; Sudireddy, Bhaskar Reddy; Blennow, Peter; Graves, Christopher
Abstract : To solve issues of coking and redox instability related to the presence of nickel in typical fuel electrodes in solid oxide cells, Gd-doped CeO2 (CGO) electrodes were studied using symmetric cells. These electrodes showed high electro-catalytic activity, but low electronic conductivity. When infiltrated with Sr0.99 Fe0.75 Mo0.25 O3-δ (SFM), the electronic conductivity was enhanced. However, polarization resistance of the cells increased, suggesting that the infiltrated material is less electro-catalytically active and was partly blocking the CGO surface reaction sites. The activity could be regained by infiltrating nano-sized CGO or NiCGO on top of SFM, while still sustaining the high electronic conductivity. Ohmic resistance of the electrodes was thus practically eliminated and performance comparable to, or better than, state-of-the-art fuel electrodes has been achieved. The Ni containing cells were damaged by carbon deposition in a CO/CO2 -atmosphere, while none of the non-nickel cells catalyzed carbon. Stability towards redox cycles was also proven.